Zertifikate im deutschen Weiterbildungssystem. Erfahrungen und Perspektiven - Ekkehard Nuissl; Ewa Przybylska (Edukacja Ustawiczna Dorosłych)
The aim of the article is to analyze current solutions in the field of certification, characteristic of German lifelong learning system. The debate on certification of competences and skills that has been going on in this country for several decades so far mainly concerned education, including higher education, and vocational education, to a lesser extent it referred to the area of lifelong education, in which greater importance has been attached to openness and flexibility in approach to learners rather than the qualifications system. The contemporary tendency to certify an increasing number of offers implemented as part of lifelong education has stimulated both social discussion about the importance of this sector in the education system as well as scientific debates, in which the emphasis is on the need to evaluate standards and certification requirements in terms of the usefulness of the solutions used, including their possible side effects, such as creating barriers to access those offers